181 PULMONARY mRNA LEVELS OF RARα AND HIF2α IN CHRONICALLY VENTILATED PRETERM LAMBS. (1st January 2005) - McKnight, R. A.; Byreddy, D. V.; Dahl, M. J.; Lane, R. H.; Albertine, K. H.
Abstract : Background: In the premature infant, volume trauma contributes to the pathogenesis of chronic lung disease, which is characterized by an arrest of secondary septation. Similarly, conventional ventilation (CV) in the preterm lamb inhibits secondary septation, whereas nasal continuous positive pressure (NCPAP) permits septation. We have recently demonstrated that vitamin A supplementation (VitA) of the preterm lamb during CV also permits septation. The transcription factor HIF2α contributes to VEGF regulated septation in the lung, but it is unknown whether HIF2 α mRNA levels respond to vitamin A treatment. Objective: We hypothesized that VitA therapy increases pulmonary HIF2 α mRNA levels in chronically ventilated preterm lambs through RAR α signaling. Methods: Preterm lambs were delivered at 132d of gestation. All lambs were treated with antenatal steroids and postnatal surfactant. The lambs were managed with NCPAP (control), CV, or CV+VitA for 72 hours. Lung tissue was harvested; DNA and RNA were isolated. Segments of the Ovis aeries HIF2 α and RAR α cDNA were cloned and sequenced. Real time RT-PCR was used to determine mRNA levels. Results: A1295 bp cDNA fragment of the sheep HIF2 α was cloned, which was 92% and 89% homologous to the human and mouse HIF2 α sequences respectively. A 516 bp DNA fragment of the sheep RAR α was cloned, which was similarly 94% and 92% homologous to the human and mouse RAR α sequences respectively. Interestingly, relative to the NCPAP controls, both CV and CV+VitA significantly decreased HIF2 α expression 65 ± 12%* and 65 ± 14%* respectively (*p ≤ 0.05). In contrast, CV+VitA increased RAR α mRNA levels to ò 160% of both NCPAP and CV. Conclusion: The cloned segments of sheep HIF2 α and RAR α were reasonably well conserved, emphasizing their evolutionary importance. Three days of CV in the preterm lamb significantly decreased pulmonary HIF2 α mRNA levels regardless of whether the lambs were treated with VitA. The lack of VitA response by HIF2 α is likely not a result of ineffectual VitA dosing, because CV+VitA increased RAR α mRNA levels. We speculate that the improved septation seen through VitA therapy of the chronically ventilated preterm lamb does not occur through transcriptional regulation of the HIF2 α gene.